Keratinocyte-intrinsic MHCII expression controls microbiota-induced Th1 cell responses - Tamoutounour, Samira; Han, Seong-Ji; Deckers, Julie; Constantinides, Michael G.; Hurabielle, Charlotte; Harrison, Oliver J.; Bouladoux, Nicolas; Linehan, Jonathan L.; Link, Verena M.; Vujkovic-Cvijin, Ivan; Perez-Chaparro, Paula Juliana; Rosshart, Stephan P.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
The cross-talk between the microbiota and the immune system plays a fundamental role in the control of host physiology. However, the tissue-specific factors controlling this dialogue remain poorly understood. Here we demonstrate that T cell responses to commensal colonization are associated with the development of organized cellular clusters within the skin epithelium. These organized lymphocyte clusters are surrounded by keratinocytes expressing a discrete program associated with antigen presentation and antimicrobial defense. Notably, IL-22–mediated keratinocyte-intrinsic MHC class II expression was required for the selective accumulation of commensal-induced IFN-γ, but not IL-17A–producing CD4+ T cells within the skin. Taking these data together, this work uncovers an unexpected role for MHC class II expression by keratinocytes in the control of homeostatic type 1 responses to the microbiota. Our findings have important implications for the understanding of the tissue-specific rules governing the dialogue between a host and its microbiota.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Antigen presentation; Keratinocyte; Microbiota; Skin; Th1